Essays on Northeastern North America, 17th & 18th Centuries. - Reid, John G. (University of Toronto Press, 2008)
The essays in this volume deal with topics such as colonial habitation, imperial exchange, and aboriginal engagement, all of which were pervasive phenomena of the time.